GERAKAN INTELEKTUAL MAHASISWA DI MASA KEJAYAAN ISLAM (GOLDEN AGE) - Ahmad Izza Muttaqin (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2013)
The heyday of Islam with the rapid growth of Islamic culture,marked by the growing breadth of Islamic educational institutionsand formal madrassas and universities in various Islamic culturalcenter. History records, progress in science Islam classical erareached its peak at the time of the Abbasid caliphs, especially duringAl Ma'mun. Advances in science prickly, may imply progress in thefield of education. This means that at the time of Islamic educationis progressing covers various fields of science, both religion andscience general science. Thullab word is the plural of Talib said. Thisword comes from the Arabic language is thalaba, yathlubu,thalaban, thalibun which means people are looking for something.Students or al Talib is a man who has has the ability to choose thepath of life, find what is judged good, trying to get the knowledge andearnest in looking for it. Student life can be seen in terms of theirdaily activities in the process of gaining knowledge. Their lives ingetting science experienced with various activities, among others:Activities Learning Directly With Sheikh, arguing Activity As anintellectual exercise, Rihlah Scientific Activities.